GAMBARAN PENGETAHUAN MAHASISWA D3 KEPERAWATAN TENTANG KERACUNAN MAKANAN DI STIKes SANTA ELISABETH MEDAN TAHUN 2021 - Connie Melva Sianipar; David Manuel Simanjuntak (ARKA INSTITUTE, 2022)
Knowledge is a participant's understanding of a given topic to receive, retain, and use information, which is influenced by experience and skills, most of the knowledge a person has comes from both formal and informal education, personal experience and other people, the environment, and the mass media. . Food serves as a vehicle for many pathogenic agents that cause what is known as food-borne illness or food poisoning. Lack of knowledge, attitudes and practices to prevent food poisoning can lead to food poisoning. Mishandled food and poor personal hygiene can cause pathogens to grow and multiply in sufficient numbers and cause disease in humans. Food poisoning is caused by a bacterial, viral, or fungal infection. The main sources of food poisoning include natural sources such as poisonous plants, chemical or metal contamination, such as pesticides and herbicides and from micro-organisms such as bacteria and viruses. The purpose of this study was to describe the knowledge of D3 Nursing students about food poisoning. The method in this research is descriptive method. The sampling technique used is a total sampling of 88 respondents. The results of the research conducted at STIKes Santa Elisabeth Medan as follows, the knowledge of D3 Nursing students at STIKes Santa Elisabeth was mostly very good, obtained as many as 62 respondents (70.5%). Knowledge of D3 Nursing students about food poisoning is in the very good category because the higher a person's education and life experience, the faster they can understand a condition.